Protein kinase inhibitors as sensitizing agents for chemotherapy - Chen, Zhe-Sheng (Jason); Yang, Dong-Hua (Cancer sensitizing agents for chemotherapy, 2019)
Tyrosine Kinase Inhibitors as Sensitizing Agents for Chemotherapy, the fourth volume in the Cancer Sensitizing Agents for Chemotherapy Series, focuses on strategic combination therapies that involve a variety of tyrosine kinase inhibitors working together to overcome multi-drug resistance in cancer cells. The book discusses several tyrosine kinase inhibitors that have been used as sensitizing agents, such as EGFR, BCR-ABL, ALK and BRAF. In each chapter, readers will find comprehensive knowledge on the inhibitor and its action, including its biochemical, genetic, and molecular mechanisms' emphases. This book is a valuable source for oncologists, cancer researchers and those interested in applying new sensitizing agents to their research in clinical practice and in trials.